(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Give this article delves into the investigation of the crystal structure and crystalline orientation of composite polyamide 6 (PA6) nanofibers. The study aims to elucidate the impact of crystallinity and crystalline orientation on the properties of composite nanofibers, which were manufactured by the electrospinning process of Nylon 6/formic acid (HCOOH) polymer solutions at concentrations of 16%, 20% and 28%, incorporating 0.25% succinite powder with particle sizes ranging from 5 to 20 nm. The average diameters of the resulting nanofiber mats were systematically measured, revealing dimensions of 50±15 nm, 90±18 nm, and 340±78 nm, respectively. Using wide-angle X-ray diffraction (WAXD) analysis, the study provides a detailed examination of how the concentration of PA6 and the inclusion of organic succinite additives influence the crystal structure and crystalline orientation within the polymer matrix. In particular, it highlights the effects observed at smaller diameters of composite nanofibers, where enhanced macromolecular alignment is coupled with reduced crystallinity, marking the first comprehensive exploration of these phenomena in individual composite nanofibers. Research demonstrates that the relative distribution of different crystalline phases varies among samples with different average diameters. Notably, the sample with the smallest average diameter of 50 nm showcased a singular crystalline peak at 2θ=21.23°, closely aligning with the theoretically reported value for the γ phase (2θ=21.4°). On the contrary, samples with larger average diameters revealed progressively more distinct shoulders on X-ray diffraction patterns, indicative of the α phase. A notable increase of approximately 25% was observed as the diameter of the composite nanofibers decreased. Furthermore, the composite nanofibers of smaller diameter presented a narrower full width at Half Maximum (FWHM), suggesting enhanced orientation for both observed phases. This study not only contributes to understanding of the influence of nanofiber composition and structure on their physical properties but also opens new avenues for the tailored design of nanofiber based composites for advanced engineering applications.